2005
DOI: 10.1073/pnas.0501312102
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone decreases renal vitamin D receptor expressionin vivo

Abstract: The vitamin D receptor (VDR) is a nuclear transcription factor responsible for mediating the biological activities of 1,25-dihydroxyvitamin D3 [1,25(OH)2D3]. Renal and parathyroid gland VDR content is an important factor in calcium homeostasis, vitamin D metabolism, and the treatment of secondary hyperparathyroidism and renal osteodystrophy. In these tissues, VDR expression is highly regulated by the calcium and vitamin D status. Although 1,25(OH)2D3 up-regulates VDR expression, hypocalcemia and vitamin D defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
(31 reference statements)
3
17
0
1
Order By: Relevance
“…In contrast, circulating PTH levels in sham female rats were not upregulated in response to LCD as usually observed in male animals. Our interpretation is consistent with the recent report by Healy et al (21) in which PTH downregulates renal VDR expression in mice. It remains unclear how ovariectomy alone may induce renal VDR expression, as it cannot be accounted for by the level of circulating PTH or 1,25(OH) 2 D 3 in OVX rats.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, circulating PTH levels in sham female rats were not upregulated in response to LCD as usually observed in male animals. Our interpretation is consistent with the recent report by Healy et al (21) in which PTH downregulates renal VDR expression in mice. It remains unclear how ovariectomy alone may induce renal VDR expression, as it cannot be accounted for by the level of circulating PTH or 1,25(OH) 2 D 3 in OVX rats.…”
Section: Discussionsupporting
confidence: 83%
“…This prior study suggested that high [Ca 2ϩ ] e treatment in HK-2G cells is counter-regulatory to the effects of PTH on VDR. These in vitro changes in VDR mirror the exact scenario that is reflective of in vivo renal VDR regulation that occur during hypo-and hypercalcemia conditions (47,51,52). It will be interesting to examine the dual impact of Ca versus PTH signaling in HK-2G cells with regard to molecular components of renal vitamin D metabolism.…”
Section: Renal P38␣ Activation By [Camentioning
confidence: 99%
“…Parathyroid hormone (PTH) is responsible for maintaining the serum level of calcium. It acts in concert with 1,25-(OH)2D3 to increase bone resorption and renal reabsorption of calcium [26,27]. As a form of negative feedback regulation, 1,25-(OH)2D3 decreases PTH levels by negative regulation of the PTH gene [28].…”
mentioning
confidence: 99%